Analysis of the links between feminist thought, political activism, and theological discourse in the struggle for social justice: The way forward - Makhanya, Monument Thulani Bongani (Stellenbosch Theological Journal, 2024)
The fight for body positivity is an ongoing struggle against unattainable beauty standards and social pressure. It entails questioning accepted norms, celebrating variety, and advocating for acceptance of all physical characteristics. It is necessary to demolish false beliefs and promote inclusivity, mental health, and self-acceptance in order to cultivate a culture of self-love and empowerment. This article therefore explores the relationships that exist between the pursuit of body positivism and feminist theory, political activity, and theological discourse. In order to oppose restrictive body norms and advance body acceptance and empowerment, it explores the intersections between feminist theories, political activism, and theological concepts. This analysis seeks to offer light on the ways in which these three characteristics contribute to the body positivist movement and its implications for global gender equality by examining historical developments, current problems, and prospective paths for change. This article utilised the secondary, feminist and liberation theologies analysis as methodology. The article has six proposals to individuals, communities, institutions, and society as a transformative strategy.